2020
DOI: 10.2166/washdev.2020.129
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of availability of handwashing facilities in households from four East African countries

Abstract: The World Health Organization provides guidelines on handwashing as part of the global campaign towards achieving proper hygiene. In East Africa, cholera and diarrhoea outbreaks and, most recently, COVID-19 remain a threat to public health – calling for the promotion of handwashing to prevent infection. Using data from demographic and health surveys in four East African countries (Kenya, Rwanda, Tanzania and Uganda), we estimate the prevalence and identify the predictors of the availability of handwashing faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…A lack of handwashing and poor personal hygiene presents a risk of infections with T. solium cysticercosis to tapeworm carriers through the direct ingestion of eggs or to other household members through contamination of food and/or water. In a review on the availability of handwashing facilities in East African countries, using demographic health surveys, Kisaakye et al ( 44 ) noted that Uganda had the least availability at 59.2%. The promotion of handwashing and improved personal hygiene is done by community leaders and VHTs, but may have not been achieving the desired impact.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of handwashing and poor personal hygiene presents a risk of infections with T. solium cysticercosis to tapeworm carriers through the direct ingestion of eggs or to other household members through contamination of food and/or water. In a review on the availability of handwashing facilities in East African countries, using demographic health surveys, Kisaakye et al ( 44 ) noted that Uganda had the least availability at 59.2%. The promotion of handwashing and improved personal hygiene is done by community leaders and VHTs, but may have not been achieving the desired impact.…”
Section: Discussionmentioning
confidence: 99%
“…Of the roughly 818 million children worldwide who lack basic hand washing facilities at school, more than onethird are in sub-Saharan Africa [6]. About 40% of the global population live without basic hand washing facilities at home [7]. The inconvenient and unfortunate truth is that the recurrent annual deaths resulting from unsafe drinking water is approximately the same as the death rate due to current Covid-19 which hopefully is not a recurrent pandemic.…”
Section: Review Articlementioning
confidence: 99%
“…Handwashing at critical times is crucial to deal with fecal contamination and improve hygiene. An assessment of availability of handwashing facilities in households from four East African countries (Tanzania, Kenya, Uganda and Rwanda) revealed that the type of residence, household wealth, number of children, age, sex and education of the household head were strong predictors of having a handwashing facility in the household [ 8 ]. A sanitation study in school settings by Okello et al [ 9 ] in Kagera region in Tanzania found that motivation for handwashing practices was enhanced by emotional drivers such as disgust, fear and nurture as well as newly established handwashing stations.…”
Section: Introductionmentioning
confidence: 99%